Assessing the effects of emerging plastics on the environment and public health - Joo, Sung Hee (Advances in human services and public health book series., 2022)
"With plastic pollution concerns growing globally, especially the production, consumption, and disposal of face masks, medical gloves, personal protective equipment and plastic dishes, this book is about assessing harmful effects of plastics on the environment and public health"--